Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1200/op.21.00401
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Provider and Survivor Experiences With Telehealth During the COVID-19 Pandemic

Abstract: PURPOSE The COVID-19 pandemic led to rapid shifts in cancer survivorship care, including the widespread use of telehealth. Given the swift transition and limited data on preferences and experiences around telehealth, we surveyed oncology providers and post-treatment survivors to better understand experiences with the transition to telehealth. METHODS We distributed provider (MD, PA or NP, nurse, navigator, and social worker) and survivor surveys through the American College of Surgeons Commission on Cancer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…Some studies found that patients’ overall satisfaction with telehealth is high [ 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Reducing exposure to COVID-19 [ 15 , 22 ], including the time- and money-saving benefits of telehealth, promotes telehealth visits as a favorable option during the pandemic [ 10 , 16 , 17 , 20 , 22 , 23 , 24 , 43 , 44 ]. Despite its benefits, some patients felt that telehealth is not a good alternative to in-person visits because it does not optimize patients’ experience (e.g., no physical examinations) (43,44), and may compromise clinician-patient relationship, cybersecurity, and health care accessibility [ 12 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies found that patients’ overall satisfaction with telehealth is high [ 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Reducing exposure to COVID-19 [ 15 , 22 ], including the time- and money-saving benefits of telehealth, promotes telehealth visits as a favorable option during the pandemic [ 10 , 16 , 17 , 20 , 22 , 23 , 24 , 43 , 44 ]. Despite its benefits, some patients felt that telehealth is not a good alternative to in-person visits because it does not optimize patients’ experience (e.g., no physical examinations) (43,44), and may compromise clinician-patient relationship, cybersecurity, and health care accessibility [ 12 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, telehealth appointments have been well received by patients, with high rates of satisfaction among patients [ 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Benefits of telehealth identified by patients included reduced exposure to COVID-19 [ 15 , 22 ] and convenience (e.g., time and money saved by avoiding travel to in-person appointments) [ 10 , 16 , 17 , 20 , 22 , 23 , 24 ]. However, this rapid shift into telehealth has substantial negative consequences in terms of clinician-patient relationships, cybersecurity and technical aspects, and health care accessibility [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This, coupled with patient concerns about COVID-19 exposure and inability to advocate for one's health resulted in delays, disruptions, or abandonment of care delivery services in some instances [36]. While cancer centers and healthcare systems have acted to mitigate the repercussions of COVID-19, some practices that we observed, such as the adoption of telemedicine, continue to exacerbate existing disparities and pose additional challenges [37][38][39]. While the long-term consequences of these various disruptions are unknown, we saw that a multifaceted strategy in collaboration with COEs, healthcare systems, community organizations, government institutions, and universities may serve as a solution to addressing disparities amplified by COVID-19 [40].…”
Section: Discussionmentioning
confidence: 88%